Occurrence and direct control potential of parasitoids and predators of the fall armyworm (Lepidoptera: Noctuidae) on maize in the subtropical lowlands of Mexico - Hoballah, Maria Elena; Degen, Thomas; Bergvinson, David; Savidan, Anita; Tamò, Cristina; Turlings, Ted (My University, 2004)
1 Native natural enemies have the potential to control fall armyworm Spodoptera frugiperda (Smith) in tropical maize grown in Mexico, where this insect pest causes severe economic losses to farmers. It has been proposed that enhancing herbivore-induced volatile emissions in maize plants may help to increase the effectiveness of natural enemies, which use these volatiles to locate their prey. This will only be of immediate benefit to farmers if the activity of the natural enemies results in a direct reduction in herbivory. Here we report on field surveys for the most common natural enemies in a tropical maize-growing region in Mexico and the potential effects of these enemies on herbivory by fall armyworm.
2 Caterpillars were collected in maize fields near Poza Rica in the state of Veracruz during January and February 1999, 2000 and 2001. Plants were either naturally infested by S. frugiperda, or artificially infested with laboratory-reared larvae. Ten species of parasitoids emerged from the collected larvae and eight species of predators that are known to feed on larvae and eggs were observed on the plants. Campoletis sonorensis (Cameron) (Hymenoptera: Ichneumonidae) was the dominant parasitoid species, in 1999 and 2001.
3 Of the nine larval parasitoids collected, six (all solitary) are known to reduce herbivory, whereas one causes the host to eat more (for two species this is not known). This implies that enhancing the effectiveness of solitary endoparasitoids may benefit subsistence farmers in developing countries by immediately reducing herbivory. The overall benefit for the plant resulting from parasitoid activity also has important implications for the evolutionary role of parasitoids in contributing to selection pressures that shape indirect defences in plants.
Keywords: Biological control; fall armyworm; maize; Mexico; pest management; Spodoptera frugiperda; parasitoids; predators